Barras de chocolate negro con la adición de NIBS de cacao (Theobroma Cacao l.) Ccn51 como un extensor alimenticio. - Ruiz Franco, Ubaldo Israel (2016)
The main was to develop black chocolate bars with the addition of four percentages of cocoa nibs CCN51, as an extender without changing the physical-chemical and sensory characteristics of the chocolate bars. A randomized complete design (DCA) was used with five treatments and 5 replicates including one control that was not added to CCN51 cocoa nibs. The variables studied were organoleptic analysis: acid taste, astringent bitter, sweet, physical-chemical analysis: percentage of protein, humidity, pH, ash, fat and microbiological analysis in the Laboratory of bromatology of the University Technical State of Quevedo. The preparation of the black chocolate bars was done by adding different percentages (10%, 20%, 30% and 40%) of CCN51 cocoa nibs. Then, the respective analyzes were performed on the bars obtained, proving that T1 was the most accepted, since this treatment was the one that was most statistically approximated to the parameters of the control such as: physical-chemical properties, organoleptic as: Cocoa odor, astringency, nut aroma, bitter, floral aroma, being able to use the percentage of T1 of cocoa nibs CCN51 as an extender without acquiring a significant organoleptic or physicochemical difference.